Scrambling and De-Scrambling Implementation Using Linear Feedback Shift Register Method on FPGA - Lurina, Manda; Hadiyoso, Sugondo; Pudji Astuti, Rina (IJAIT (International Journal of Applied Information Technology), 2017)
Digital broadband communications require a fast, functional and efficient system. In a digital communication system, a long sequence of bits '0' or '1' will inherits the loss of bit synchronization, and hence it can cause the false detection on the receiver. To avoid this, long sequence of bits will be randomized first so that long sequence of bits '0' or '1' can be removed. This randomization process is called scrambling and the circuit that works for the process is a scrambler. In the receiver there is a descrambler that serves to return the bits to their original information. This paper presents a design of scrambler and descrambler using a combination of Linear Feedback Shift Register (LFSR) with 15 registers, XOR logic gates, and Pseudo Random Binary Sequence (PRBS) generator structure with polynomial 1 + x14 + x15. One of the two main parts of LFSR is the shift register while the other is the feedback. In LFSR, the bits contained within the selected position in the shift register will be combined in a function and the result will be put back into this register's input bit. Feedback also makes the system more stable and no error occurrence. Then special tap is taken from a certain point in XOR and returned as a feedback register. The system is implemented on FPGA board Altera De0-Nano EP4CE22F17C6 Cyclone IV E. Resource memory required <1% of available memory. Bit rate that can be achieved with clock speed 50MHz is 335570.47 bps.